2019
DOI: 10.1007/s12079-019-00536-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Wnt1-inducible signaling pathway protein-1 (WISP-1/CCN4) is a novel biomarker of adiposity in subjects with type 2 diabetes

Abstract: Background Wnt1-inducible signaling pathway protein 1, or cellular communication network factor 4 (CCN4), a member of CCN family of secreted, extracellular matrix associated signaling proteins, recently was validated as a novel adipose tissue derived cytokine. Objective To assess the relationships between circulating CCN4, adipose tissue distribution and function, and chronic low-grade inflammation in subjects with type 2 diabetes. Methods We observed 156 patients with type 2 diabetes and 24 healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
5
11
0
1
Order By: Relevance
“…serum WISP1 levels independently contribute to LEAD in patients with newly diagnosed T2DM. When comparing previously published data from Hörbelt et al [12], Klimontov et al [13], and Tacke et al [17], we reported relatively high levels of WISP1 in our cohort. According to the study of Tacke et al [17], WISP1 levels in serum samples were higher than that in plasma.…”
Section: Characteristicssupporting
confidence: 82%
“…serum WISP1 levels independently contribute to LEAD in patients with newly diagnosed T2DM. When comparing previously published data from Hörbelt et al [12], Klimontov et al [13], and Tacke et al [17], we reported relatively high levels of WISP1 in our cohort. According to the study of Tacke et al [17], WISP1 levels in serum samples were higher than that in plasma.…”
Section: Characteristicssupporting
confidence: 82%
“…Further, in the HSC model, exposure to CCN4 caused a dose-dependent induction of fibrosis markers and proinflammatory cytokines alone or in combination with TGF-β treatment. These findings extend our previous studies showing the functions of CCN4 in insulin resistance and inflammation [ 15 , 16 , 17 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our previous work, CCN4 mRNA expression in VAT showed a positive correlation with CCL2 expression in a cohort of normal-weight and obese subjects [ 16 ]. In a cohort of subjects with type 2 diabetes, the circulating CCN4 levels correlated positively with fat mass, serum leptin, resistin, and visfatin levels [ 26 ], suggesting that CCN4 may contribute to the metabolically-induced tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the association of WISP-1 and type 2 diabetes mellitus. Klimontov et al demonstrated significantly higher serum levels of WISP-1 in the group of subjects diagnosed with type 2 diabetes mellitus than in healthy controls [ 38 ]. In contrast, a study comparing circulating levels of WISP-1 in the group of men with obesity with and without type 2 diabetes mellitus revealed no significant difference [ 29 ].…”
Section: Wisp-1 and Diabetesmentioning
confidence: 99%